Aseptic Otogenic Lateral Sinus Thrombosis – A case report (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: In pre-antibiotic era Lateral Sinus Thrombosis (LST) was the second most common intracranial complication of otitis media with almost 100 % mortality. Now the trend has been changed. Easy availability of antibiotics has made this complication very rare. Mortality rate is also drastically reduced with alteration of the presentation of the disease. Objectives: The aim of this case report is to focus on the altered presentation of the disease, do analysis and explain the reasons behind that. Case Summary: It was a 65 years old, physically well build & psychologically sound gentleman admitted in the department of ENT-Head & Neck Surgery through Emergency with severe pain in left temporal region and concomitant history of discharge from Left ear in October, 2023. He was diagnosed as a case of LST otogenic in origin on MRI and MRV of brain. Conclusions: Otogenic LST, though has become a rare entity, can still happen with different presentation. Therefore, keeping a high level of suspicion is essential for any patient coming with severe earache and middle ear infection. Though antibiotics are available as OTC (over the counter)choosing a wrong antibiotic, not adequate in terms of dosage and duration; candirectthe clinical course towards a potentially dangerous catastrophe.Bangladesh J Otorhinolaryngology 2024; 30(1): 39-43